Clinical Diffusion Mismatch to Select Pediatric Patients for Embolectomy 6 to 24 Hours After Stroke: An Analysis of the Save ChildS Study. (19th January 2021) - Sporns, Peter B.; Psychogios, Marios-Nikos; Straeter, Ronald; Hanning, Uta; Minnerup, Jens; Chapot, René; Henkes, Hans; Henkes, Elina; Grams, Astrid; Dorn, Franziska; Nikoubashman, Omid; Wiesmann, Martin; et al.
Abstract : Objective: To determine whether thrombectomy is safe in children up to 24 hours after onset of symptoms when selected by mismatch between clinical deficit and infarct. Methods: A secondary analysis of the Save ChildS Study (January 2000–December 2018) was performed, including all pediatric patients (<18 years) diagnosed with arterial ischemic stroke who underwent endovascular recanalization at 27 European and United States stroke centers. Patients were included if they had a relevant mismatch between clinical deficit and infarct. Results: Twenty children with a median age of 10.5 (interquartile range [IQR] 7–14.6) years were included. Of those, 7 were male (35%), and median time from onset to thrombectomy was 9.8 (IQR 7.8–16.2) hours. Neurologic outcome improved from a median Pediatric NIH Stroke Scale score of 12.0 (IQR 8.8–20.3) at admission to 2.0 (IQR 1.2–6.8) at day 7. Median modified Rankin Scale (mRS) score was 1.0 (IQR 0–1.6) at 3 months and 0.0 (IQR 0–1.0) at 24 months. One patient developed transient peri-interventional vasospasm; no other complications were observed. A comparison of the mRS score to the mRS score in the DAWN and DEFUSE 3 trials revealed a higher proportion of good outcomes in the pediatric compared to the adult study population. Conclusions: Thrombectomy in pediatric ischemic stroke in an extended time window of up to 24 hours after onset of symptoms seems safe and neurologic outcomes are generally good if patients are selected by a mismatch between clinical deficit and infarct. Classification of Evidence: This study provides Class IV evidence that for children with acute ischemic stroke with a mismatch between clinical deficit and infarct size, thrombectomy is safe.